(untitled) - Bacharach, Michael (London, 1976)
The book is so arranged that the specifically economic material can be omitted by the non-economist reader.The same goes for the few passages that demand more than elementary mathematical skills.
Keywords: Game theory,Economics, Mathematical,Lý thuyết trò chơi,Kinh tế, Toán học